2002
DOI: 10.1093/rheumatology/41.3.346-a
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate in the treatment of avascular necrosis of the hip

Abstract: Alendronate in the treatment of avascular necrosis of the hip SIR, Avascular necrosis (AVN) of the bone results from decreased blood supply to the bone, resulting in bone death. The most common site is the head of the femur. AVN is characterized by persistent, often nagging and disabling pain associated with significant reduction in joint movement and mobility. The condition tends to run a progressively downhill course. Medical and surgical management generally aims to improve the blood supply by vasodilators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 3 publications
1
50
0
3
Order By: Relevance
“…It is suspected that smoking, 32 chronic use of alcohol, 32,36 diabetes mellitus, 11 hypoproteinemia, 4 corticotherapy, chemotherapy, 6,12,14,15,37,38 immunosuppressive therapy, 12,36 endodontic lesions, periodontal disease, abscesses, 9 poor oral hygiene, 32 and renal insufficiency 27 are cofactors in the development of osteonecrosis by bisphosphonates. Therefore, it is necessary to consider that in the case of alendronate, 1 or more cofactors could exert an essential role in the development of osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is suspected that smoking, 32 chronic use of alcohol, 32,36 diabetes mellitus, 11 hypoproteinemia, 4 corticotherapy, chemotherapy, 6,12,14,15,37,38 immunosuppressive therapy, 12,36 endodontic lesions, periodontal disease, abscesses, 9 poor oral hygiene, 32 and renal insufficiency 27 are cofactors in the development of osteonecrosis by bisphosphonates. Therefore, it is necessary to consider that in the case of alendronate, 1 or more cofactors could exert an essential role in the development of osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of successful bisphosphonate treatment of the transient osteoporosis of the hip or osteonecrosis of the femoral head [1,2,14,29,36,37,43,50]. In an uncontrolled clinical study, 16 patients with avascular necrosis of the hip were treated with alendronate and an improvement in pain, disability and function compared to the expected natural history of the disease was found [3]. In a recently published observation from the same authors of 395 hips with avascular necrosis which were treated with alendronate for 3 years with a mean follow-up of 4 years improvement in the clinical function, a reduction in the rate of collapse and a decrease in the requirement for total hip replacement, compared with the findings of other studies in which no treatment was given [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although changes in urinary NTX did not have any significant correlation with changes in FSS in the present study, one possibility for the mechanisms may be concerned with bone resorption, because the efficacy of bisphosphonates for bone pain in patients with bone resorption-related diseases has been demonstrated. Agarwala et al [33] reported that short-term treatment with ALN improved pain, disability, and standing and walking capacity in patients with avascular necrosis of the hip, due to inhibition of the resorptive action of mature osteoclasts, an increase in apoptosis of osteoclasts, and probably a decrease in apoptosis of osteoblasts and osteocytes. Intravenous pamidronate seems to be a valuable treatment for back pain, as well as rehabilitating elderly patients suffering from chronic and refractory back pain due to osteoporotic vertebral fractures [34], and also for reduction of skeletal pain and biochemical markers of bone resorption in patients with skeletal metastases [35][36][37].…”
Section: Discussionmentioning
confidence: 99%